2018
DOI: 10.1093/abbs/gmy097
|View full text |Cite
|
Sign up to set email alerts
|

Tafa-2 plays an essential role in neuronal survival and neurobiological function in mice

Abstract: Tafa is a family of small secreted proteins with conserved cysteine residues and restricted expression in the brain. It is composed of five highly homologous genes referred to as Tafa-1 to -5. Among them, Tafa-2 is identified as one of the potential genes responsible for intellectual deficiency in a patient with mild mental retardation. To investigate the biological function of Tafa-2 in vivo, Tafa-2 knockout mice were generated. The mutant mice grew and developed normally but exhibited impairments in spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Emerging evidence has indicated that FAM19A family is involved in the pathological mechanism of cognition. FAM19A2 knockout mice exhibited decline in short-term and long-term memory via novel object recognition test and decline in spatial learning and memory via the Morris water maze (MWM) test [26,27]. However, FAM19A1 knockout mice only exhibited reduced anxiety and sensitivity to pain, and spatial learning and exploration are preserved [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that FAM19A family is involved in the pathological mechanism of cognition. FAM19A2 knockout mice exhibited decline in short-term and long-term memory via novel object recognition test and decline in spatial learning and memory via the Morris water maze (MWM) test [26,27]. However, FAM19A1 knockout mice only exhibited reduced anxiety and sensitivity to pain, and spatial learning and exploration are preserved [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the increased axon outgrowth by CH02 primarily depended on regulating AKT signaling downstream of FGFRs. Since ERK and AKT as pro-survival signaling molecules were implicated in regulating neuronal survival 66 - 69 , we determined whether CH02- mediated-enhanced neuron survival depended on the AKT or ERK signal downstream of FGFRs. We observed that both AKTi and U0126 significantly reduced the protective effect of CH02 on neurons from apoptosis induced by H 2 O 2 (Figure 6 M-N).…”
Section: Resultsmentioning
confidence: 99%
“…FAM19A1 is a ligand for GPR1 (G protein-coupled receptor 1), that has a function in the proliferation and self-renewal of neural stem cells. [22][23][24] The FAM19A1 gene has a HI of 8%; consequently, this partial deletion could contribute to development delay and hypotonia.…”
Section: Discussionmentioning
confidence: 99%